Individual differences in proactive interference in rats (Rattus Norvegicus) - Phil Reed (Psychonomic Bulletin & Review, 2022)
Individual differences in behaviors are seen across many species, and investigations have focused on traits linked to aggression, risk taking, emotionality, coping styles, and differences in cognitive systems. The current study investigated whether there were individual differences in proactive interference tasks in rats (Rattus Norvegicus), and tested hypotheses suggesting that these tasks should load onto a single factor and there should be clusters of rats who perform well or poorly on these tasks. The performance of 39 rats was tested across three learning tasks that all involved disengagement from an irrelevant previously learned stimulus to a relevant stimulus: latent inhibition (LI), partial reinforcement extinction effect (PREE), and reversal learning (RL). An exploratory factor analysis revealed the existence of one factor underlying performance. A cluster analysis revealed the existence of sets of rats displaying either weak LI and strong PREE and RL effects, or vice versa. These findings suggest that proactive interference may be based on a single underlying psychological system in rats.